Estimating the Lateral Distribution Function of Cerenkov Light as a Function of the Primary Energy for the Chacaltaya EAS Array (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
A new method for estimating the energy and the mass composition of primary cosmic radiation based on atmospheric Cerenkov light lateral distribution function (LDF) analyzis is proposed. The Cerenkov light LDF in extensive air showers (EAS) initiated by primary protons and iron nuclei are simulated with CORSIKA code for the Chacaltaya EAS array with the different energies around the knee region with two zenith angles (0o,15o). Sets of approximate functions are constructed for two particles as a function of the primary energy based on the findings of the LDF numerical simalution. At the energies (1015–1016) eV, a comparison of the parametrised LDF with that simulated by the Chacaltaya EAS array is confirmed